Evidence for the slow reaction of hypoxia-inducible factor prolyl hydroxylase 2 with oxygen. - Flashman, E; Hoffart, L; Hamed, R; Bollinger, J; Krebs, C; Schofield, C (2010)
The response of animals to hypoxia is mediated by the hypoxia-inducible transcription factor. Human hypoxia-inducible factor is regulated by four Fe(II)- and 2-oxoglutarate-dependent oxygenases: prolyl hydroxylase domain enzymes 1-3 catalyse hydroxylation of two prolyl-residues in hypoxia-inducible factor, triggering its degradation by the proteasome. Factor inhibiting hypoxia-inducible factor catalyses the hydroxylation of an asparagine-residue in hypoxia-inducible factor, inhibiting its transcriptional activity. Collectively, the hypoxia-inducible factor hydroxylases negatively regulate hypoxia-inducible factor in response to increasing oxygen concentration. Prolyl hydroxylase domain 2 is the most important oxygen sensor in human cells; however, the underlying kinetic basis of the oxygen-sensing function of prolyl hydroxylase domain 2 is unclear. We report analyses of the reaction of prolyl hydroxylase domain 2 with oxygen. Chemical quench/MS experiments demonstrate that reaction of a complex of prolyl hydroxylase domain 2, Fe(II), 2-oxoglutarate and the C-terminal oxygen-dependent degradation domain of hypoxia-inducible factor-alpha with oxygen to form hydroxylated C-terminal oxygen-dependent degradation domain and succinate is much slower (approximately 100-fold) than for other similarly studied 2-oxoglutarate oxygenases. Stopped flow/UV-visible spectroscopy experiments demonstrate that the reaction produces a relatively stable species absorbing at 320 nm; Mössbauer spectroscopic experiments indicate that this species is likely not a Fe(IV)=O intermediate, as observed for other 2-oxoglutarate oxygenases. Overall, the results obtained suggest that, at least compared to other studied 2-oxoglutarate oxygenases, prolyl hydroxylase domain 2 reacts relatively slowly with oxygen, a property that may be associated with its function as an oxygen sensor. Structured digital abstract * MINT-7987711: PHD2 (uniprotkb:Q9GZT9) enzymaticly reacts (MI:0414) CODD (uniprotkb:Q16665) by enzymatic study (MI:0415).